A non‐destructive tissue sampling technique for holothurians to facilitate extraction of DNA for genetic analysis. Issue 3 (6th August 2015) - Nowland, Samantha J.; Jerry, Dean R.; Southgate, Paul C.
Abstract Increasing demand and overfishing of high‐value species has promoted interest in both conservation and aquaculture initiatives supporting stock restoration programs for tropical sea cucumbers. Accordingly, there is a need for baseline information on the genetic structures and relatedness of sea cucumber populations to support sustainable implementation of mariculture and conservation programs, which often involve coastal communities in developing countries. Identification of a non‐destructive tissue sampling technique for sea cucumbers that allows extraction of high‐quality genomic DNA in a sustainable and culturally appropriate way is thus required. Six sampling techniques were assessed for their suitability to collect tissue for DNA extraction from sandfish (Holothuria scabra): core needle biopsy, punch biopsy, shave biopsy, buccal swab, anal swab, and evisceration. The quantity, quality, and purity of extracted DNA were compared to assess the relative merit of each sampling method. The swab biopsy method produced the best quality DNA agarose band image, and evisceration resulted in the highest yields of DNA, at an average of 525.9 (±98.0) μg g−1. However, when considering all criteria assessed, the swab biopsy methods (both buccal and anal) proved superior. Swabbing not only produced the best quality DNA agarose band image, it was also the only technique that produced DNA that amplified 100% of the time across both extraction protocols. We hope that the non‐destructive sampling techniques evaluated in this study provide a foundation for the genetic analysis of sea cucumber stocks to support their conservation and management.